MUSCULOSKELETAL DISORDERS AND WORK STRESS IN THE HEALTH STAFF AT THE SULAB DAY HOSPITAL, QUITO- 2023 - Lizeth Carolina Sanguña Muzo; Daniel Villacís López; Oswaldo Jesús Martínez-Padrón; Navarrete Arboleda Edmundo Daniel (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Occupational health is a primary concern in work environments characterized by high levels of stress and physical demands. In this context, musculoskeletal disorders (MSDs) emerge as a relevant aspect due to their ability to impact the quality of life and work efficiency of employees. This study aimed to analyze the relationship between MSDs and job stress among healthcare personnel at the SULAB Day Hospital in Quito, Ecuador, during the year 2023. To this end, a quantitative study with a descriptive-correlational-cross-sectional design was conducted. MSDs were assessed using two instruments: the Nordic Questionnaire to detect musculoskeletal symptoms and their functional impact, and the REBA method to evaluate ergonomic risk. Additionally, the ILO-WHO Occupational Stress Survey was used to measure stress levels. The study revealed that 50.0% of healthcare workers experienced MSDs with a medium level of risk. Furthermore, 27.4% were perceived to have a high risk. Regarding job stress, attending physicians were the most affected, with 60.5% experiencing high stress levels and 13.2% experiencing very high levels. Registered nurses also showed considerable exposure, with 75.1% experiencing high stress and 21.4% experiencing very high stress levels. The findings underscore the need to implement stress management measures and their relationship with MSDs, as a significant correlation was found with a value of p = .024 < .05. This level of significance is reinforced by the correlation found (Rho = .287), indicating a positive and direct relationship, suggesting that as MSDs increase, so does job stress, and bilateral.